Transient Electronic Transport Properties through a Quantum Dots Ring - A. Abdul-Hussein, W. (International Journal of Engineering and Technology, 2018)
In this paper a theoretical study of the effect of the electron transport in a quantum dot ring, which is consisted from four quantum dots, connected with two electrode metal. For this purpose, a single-electron model was used in this system. The Hamiltonian of this system is consisted from a single level for each quantum dots. The influence of energy levels of the electrode metal was taken into consideration. The Time-dependent equations of motion were found using the Laplace transform, which was enabled the occupation-probability to be found for the right electrode. Results shown that the occupation-probability and the current flowing exhibit oscillations in the elementary stage of the transport process and finally progress into stationary values. So, the occupation probability of the R-electrode increased with the coupling interaction of the QDs and the bias voltage, but it is reduced by increasing the electrodes-QDs interaction and absolute temperature.Â Â